Iron quartzites of the Simandou mountain (Republic of Guinea) - Alexander V. Bolonin; Vladimir I. Mamedov; Igor K. Myznikov (Руды и металлы)
In this article, we for the first time fully describe the geology and petrography of the iron quartzite formation, localized in Southeast Guinea in the Simandou mountain range. In this region, a meridional distribution belt of banded magnetite quartzites (itabirite) of the Lower Proterozoic Simandou metamorphic series has been mapped. The rocks form an extended (210 km) and narrow (0.4–7 km) complex synclinal structure in the background of the Archean granite-gneiss basement. The structure of the Simandou metamorphic series includes the lower sequence of metaterrigenous rocks up to 400–500 m thick (metasandstone, quartzite, phyllite, mica schist) and the upper itabiritic sequence up to 220–450 m thick. The metamorphism of the rocks of the series increases from north to south from the greenschist to epidote-amphibolite facies. Members of two varieties of banded iron rocks are distinguished in the itabiritic stratum – itabirite and amphibole itabirite. The composition of itabirite is (wt %): magnetite 51–55, quartz 48–36, and the rest is cummingtonite and mica. The composition of amphibole itabirite is (wt %): magnetite 39–47, quartz 31– 30, amphibole (cummingtonite) 24–15, the rest is hedenbergite, mica and calcite. Rich martite and hematite-goethite ores (60–66% Fe) are formed in the lateritic weathering crust after itabirite, forming manto deposits with a depth of 9 to 350 m.